Thern,al requirernents lar the develapment of the nenialagenic lungi Paecilomyces /ilac!nus. - Fioretto, Ada Marina Cagliari; Villacorta, Amador (Pesquisa Agropecuaria Brasileira, 2013)
The fungus Paeci/omyces Iflacinus (Thom.) Samson was inoculaled and cultured on potato dexirose agar medium ai eleven different temperature leveis, ranging from 5 0C to 350C for eight days. The technique used lo evaluate lhe growth performance ol the lungus coiony on the surface mediurn was the radial surlace growth. The temperatures 5 0C and 350C proved lo be biostallc, and lhe ternperatures of 24 0C and 250C were considered as oplimum for maximum fungus growth, since they did not differ significantiy (P = 0,05). Lower temperature Uireshoid of deveiopmenl, 10,9 0C, was estimatnd by using linear regression; hence Iowertemperatures were considered lo be more suitabie for storage 01 P. Iilacinus.